2006
DOI: 10.1002/macp.200500516
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Atom Transfer Radical Polymerization with Bifunctional Initiators: Diffusion Effects and Case Studies

Abstract: Summary: A mathematical model for atom transfer radical polymerization (ATRP) with bifunctional initiators was developed. The model was validated with three case studies in bulk and solution polymerization. We used only polymer yield data to estimate some of the model parameters, while others were obtained from the literature. The model fits the polymer yield data and also predicts weight‐average molecular weights and polydispersities very well. The free volume theory was also incorporated to the model to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Chain-length dependence of reactions among large macromolecules was considered by using a number and a weight average kinetic rate coefficient for such reactions. Exactly the same modeling approach was later used by Al-Harthi et al [165] and some case studies were investigated. Their model showed that diffusion-limited termination reactions produce polymers with smaller polydispersities, while diffusion-limited propagation reactions have the opposite effect.…”
Section: A Case Study -Reversible Addition-fragmentation Transfer Polmentioning
confidence: 98%
“…Chain-length dependence of reactions among large macromolecules was considered by using a number and a weight average kinetic rate coefficient for such reactions. Exactly the same modeling approach was later used by Al-Harthi et al [165] and some case studies were investigated. Their model showed that diffusion-limited termination reactions produce polymers with smaller polydispersities, while diffusion-limited propagation reactions have the opposite effect.…”
Section: A Case Study -Reversible Addition-fragmentation Transfer Polmentioning
confidence: 98%
“…A large literature is available on the chemistry of LFRP and several of LFRP features have been elucidated with the help of mathematical models. For instance, the method of moments was used to describe NMP,8,9 ATRP10–13 and RAFT14 in batch reactors, and NMP, ATRP15,16 and RAFT17 in semi‐batch and continuous reactors; Predici was also used to study NMP,18 ATRP19–21 and RAFT22 in batch reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3A shows the logarithm of the initial apparent rate constants plotted against log(K ATRP ) for an ATRP system with four different propagation rate constants (representing four different monomers) and k t calculated from the composite model (Equation [14][15][16][17]. As expected, the apparent rate constant increases with K ATRP , but a …”
Section: Resultsmentioning
confidence: 62%
“…in the case of a static equilibrium (i.e., constant activation and deactivation rates), even in cases where the equilibrium is strongly shifted toward the dormant species due to very low equilibrium constants. Figure 3A, with k t calculated with the composite model (Equation [14][15][16][17]. The ''original k a '' series is the same as the simulated ATRP system with MMA in Figure 3A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation